Sulfated galactans from the red seaweed Gracilaria fisheri exerts anti-migration effect on cholangiocarcinoma cells - Sae-Lao, Thannicha; Luplertlop, Natthanej; Janvilisri, Tavan; Tohtong, Rutaiwan; Bates, David O; Wongprasert, Kanokpan (Elsevier, 2017)
BACKGROUND: Seaweeds have a long history of use in Asian countries as functional foods, medicinal herbs, and the treatment of cancer. Polysaccharides from various seaweeds have shown anti-tumor activity. Cholangiocarcinoma (CCA), often with metastatic disease, is highly prevalent in Thailand as a consequence of liver fluke infection. Recently, we extracted sulfated galactans (SG) from Gracilaria fisheri (G. fisheri), a south east Asian seaweed, and found it exhibited anti-proliferation effect on CCA cells. PURPOSE: In the present study, we evaluated the anti-migration activity of SG on CCA cells and its underlined mechanism. METHODS: CCA cells were treated with SG alone or drugs targeting to epidermal growth factor (EGF) receptor (EGFR) or pretreated with SG prior to incubation with EGF. Anti-migration activity was determined using a scratch wound-healing assay and zymography. Immunofluorescence staining and western blotting were used to investigate EGFR signaling mediators. RESULTS: Under basal condition, SG reduced the migration rate of CCA, which was correlated with a decrease in the active-form of matrix metalloproteinases-9. SG decreased expression of phosphorylated focal adhesion kinase (FAK), but increased expression of E-cadherin to promote cells stasis. Moreover, phosphorylation of EGFR and extracellular signal-regulated kinases (ERK), known to stimulate growth of cancer cells, was blocked in a comparable way to EGFR inhibitors Cetuximab and Erlotinib. Pretreatment cells with SG attenuated EGF induced phosphorylation of EGFR, ERK and FAK. CONCLUSION: This study reveals that SG from G. fisheri retards migration of CCA cells, and its mechanism of inhibition is mediated, to some extent, by inhibitory effects on MAPK/ERK signal transduction pathway. Our findings suggest that there may be a therapeutic potential of SG in CCA treatment.